Roman Stoicism : being lectures on the history of the Stoic philosophy with special reference to its development within the Roman Empire - Arnold, Edward Vernon, 1857-1926 (Salt Lake City, UT : Project Gutenberg, 2021)
"Roman Stoicism" by Edward Vernon Arnold is a scholarly examination of Stoic philosophy, particularly its development within the Roman Empire, written in the early 20th century. The text offers a thorough exploration of Stoicism's historical significance, philosophical doctrines, and its influence on later thought and religions. By framing Stoicism as a vital link between ancient and modern philosophies, Arnold emphasizes its relevance to contemporary discussions of morality and governance. The opening of the work outlines the foundational premises of Stoicism and situates it within the broader context of world religions. Arnold begins by explaining how Roman literature reflects deep philosophical inquiries characteristic of the Stoics, particularly concerning fate, morality, and the nature of the divine. He highlights the importance of understanding the interplay between these philosophical questions and the socio-political landscape of the Roman world. The author sets the stage for a detailed exploration of the Stoic philosophy's evolution, its interaction with other religious and philosophical traditions like Judaism and Christianity, and its enduring legacy in Western thought. (This is an automatically generated summary.)
The world-religions -- Heraclitus and Socrates -- The Academy and the Porch -- The preaching of Stoicism -- The Stoic sect in Rome -- Of reason and speech -- The foundations of physics -- The universe -- The supreme problems -- Religion -- The kingdom of the soul -- The law for humanity -- Daily duties -- Sin and weakness -- Counsels of perfection -- Stoicism in Roman history and literature -- The Stoic strain in Christianity -- Bibliography.
Release date is 2021-02-07
Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/Canadian Libraries)
Keywords: Stoics